Edaphic filters and the functional structure of plant assemblages in grasslands in southern Brazil. (11th August 2015) - Moraes, Daniele A.; Cavalin, Pedro O.; Moro, Rosemeri S.; Oliveira, Ricardo A.C.; Carmo, Marta R.B.; Marques, Marcia C.M.
Abstract: Questions: We analysed trait convergence and trait divergence assembly patterns across a metacommunity of grassland types (dry, wet and rocky) occurring along an edaphic gradient. We asked whether (1) floristics and phylogenetic structures vary among grassland types; (2) there is convergence and/or divergence in plant traits along the gradient; (3) the functional structure is influenced by phylogeny; and (4) abiotic or biotic filters generate the assembly patterns. Location: Campos Gerais region, Paraná State, southern Brazil (ca. 25°15′02″ S, 49°59′59″ W). Methods: We sampled plant functional traits and soil variables at 81.1‐m 2 quadrats in three natural grassland vegetation types across three different sites. We analysed the relationship between species composition (abundance), phylogenetic relationships, functional traits and soil characteristics using matrix correlations, where soil characteristics were the predictors of functional and phylogenetic assembly patterns. Results: A total of 168 plant species were sampled on the three vegetation types. Wet grassland quadrats were more similar to each other in species composition and phylogeny than with those on dry and rocky grasslands. We found trait convergence (not phylogenetically constrained) and trait divergence (phylogenetically constrained) assembly patterns in the three vegetation types along the edaphic gradient. Traits that generated convergence and divergence are related to strategies for survival in dry and low nutrient availability soils; nutritional soil gradient determined trait differences at small scales. Conclusion: Species composition and phylogenetic structure of communities occurring in different grassland types are related to edaphic gradient. The occurrence of both trait convergence and trait divergence patterns suggests, respectively, that environmental filters and biotic filters (competition) are structuring the plant assemblages. Abstract : This study shows that diversification in grassland types (wet, dry and rocky) are strongly related to edaphic gradient. Species occurring along the gradient presented trait specialization related to strategies for survival in dry and with low nutrient availability soils. The occurrence of trait convergence and divergence suggests that environmental and biotic filters (competition) are structuring the plant assemblages.